Robust gene expression changes in the ganglia following subclinical reactivation in rhesus macaques infected with Simian Varicella Virus - Arnold, Nicole (J Neurovirol, 2017)
Varicella zoster virus (VZV) causes varicella during acute infection and establishes latency in the sensory ganglia. Reactivation of VZV results in herpes zoster, a debilitating and painful disease. It is believed that VZV reactivates due to a decline in cell-mediated immunity; however, the roles that CD4 versus CD8 T cells play in the prevention of herpes zoster remain poorly understood. To address this question, we used a well-characterized model of VZV infection where rhesus macaques are intrabronchially infected with the homologous simian varicella virus (SVV). Latently infected rhesus macaques were thymectomized and depleted of either CD4 or CD8 T cells to induce selective senescence of each T cell subset. After T cell depletion, the animals were transferred to a new housing room to induce stress. SVV reactivation (viremia in the absence of rash) was detected in 3 out of 6 CD8-depleted and 2 out of 6 CD4-depleted animals suggesting that both CD4 and CD8 T cells play a critical role in preventing SVV reactivation. Viral loads in multiple ganglia were higher in reactivated animals compared to non-reactivated animals. In addition, reactivation results in sustained transcriptional changes in the ganglia that enriched to gene ontology and diseases terms associated with neuronal function and inflammation indicative of potential damage as a result of viral reactivation. These studies support the critical role of cellular immunity in preventing varicella virus reactivation and indicate that reactivation results in long-lasting remodeling of the ganglia transcriptome.